2009
DOI: 10.3748/wjg.15.1990
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of flow and mixing at the duodenal stump after gastric resection

Abstract: AIM:To investigate the flow and mixing at the duodenal stump after gastric resection, a computer simulation was implemented. METHODS:Using the finite element method, two different Billroth Ⅱ procedure cases (A and B) were modeled. Case A was defined with a shorter and almost straight duodenal section, while case B has a much longer and curved duodenal section. Velocity, pressure and food concentration distribution were determined and the numerical results were compared with experimental observations. RESULTS:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…In comparison, the average pressure in the small intestine is merely 0.40-0.53 kPa (3.5-4.5 mmHg). [58] These results further confirmed that the SSAD-Patch exhibited favorable adhesive abilities even under extreme conditions.…”
Section: Proof-of-principle Applications Of Ssad-patch Ex Vivosupporting
confidence: 68%
“…In comparison, the average pressure in the small intestine is merely 0.40-0.53 kPa (3.5-4.5 mmHg). [58] These results further confirmed that the SSAD-Patch exhibited favorable adhesive abilities even under extreme conditions.…”
Section: Proof-of-principle Applications Of Ssad-patch Ex Vivosupporting
confidence: 68%
“…And, all of them were reconstructed by the Billroth II method. Using manometry equipment, Filipovic et al have reported that the intraluminal duodenal stump pressure after gastrectomy reconstructed by the Billroth II method, which forms a blind loop, was higher than that at the preoperative state [14]. Moreover, the longer afferent loop reportedly caused the increase in the intraduodenal stump pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work using computerized manometry and mathematical models has demonstrated that the length of the afferent duodenal section associated with the duodenal stump has important implications for pressure distribution, food mixing, and appropriate transport [11]. Longer duodenal sections, while reducing the risk of retrograde food mixing in the direction of the stump, also led to higher stump pressures, with maximal pressure at the point of duodenal closure.…”
Section: Distal Obstructionmentioning
confidence: 99%